The impact of landslides on local infrastructure and the environment - Skrzypczak, Izabela; Kokoszka, Wanda; Kogut, Janusz (International Conference “Environmental Engineering”, 2017)
Landslides are environmental processes that lead to natural disasters or technical failures, the effects of which usually threaten the life, health and property of people. In the classification of natural disasters and hazards that occur in the world, landslides are in fifth place, both in the number of casualties and material losses. Continuous surveillance and risk assessment is a very important issue in preventing the effects of natural disasters. The paper presents the causes of landslides, the classification of landslides, several examples of landslides and damage caused by landslides. Here, the occurrence of landslides as climatic events is given, as well as geological and anthropogenic factors of landslides. The paper indicates risk assessment methods in case of landslide hazard. The risk analysis developed here is presented for selected landslides from the Subcarpathian province.